2015
DOI: 10.1002/2014wr015814
|View full text |Cite
|
Sign up to set email alerts
|

Regional flood frequency analysis at the global scale

Abstract: The characterization of flood behavior in data poor regions has been receiving considerable attention in recent years. In this context, we present the results of regional flood frequency analyses (RFFA) conducted using a global database of discharge data. A hybrid-clustering approach is used in conjunction with a flood-index methodology to provide a regionalized discharge estimates with global coverage. The procedures are implemented with varying complexity, with results indicating that catchment area and aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
154
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(174 citation statements)
references
References 58 publications
5
154
1
Order By: Relevance
“…Linear or power (often linearised through a log-transformation) forms, with either a multiplicative or additive error term, are the most commonly used functions (see e.g. Stedinger and Tasker, 1985;GRE-HYS, 1996;Pandey and Nguyen, 1999;Brath et al, 2001;Kjeldsen et al, 2001Kjeldsen et al, , 2014Bocchiola et al, 2003;Merz and Bloeschl, 2005;Griffis and Stedinger, 2007;Archfield et al, 2013;Smith et al, 2015).…”
Section: E Toth: Estimation Of Flood Warning Runoff Thresholds In Unmentioning
confidence: 99%
“…Linear or power (often linearised through a log-transformation) forms, with either a multiplicative or additive error term, are the most commonly used functions (see e.g. Stedinger and Tasker, 1985;GRE-HYS, 1996;Pandey and Nguyen, 1999;Brath et al, 2001;Kjeldsen et al, 2001Kjeldsen et al, , 2014Bocchiola et al, 2003;Merz and Bloeschl, 2005;Griffis and Stedinger, 2007;Archfield et al, 2013;Smith et al, 2015).…”
Section: E Toth: Estimation Of Flood Warning Runoff Thresholds In Unmentioning
confidence: 99%
“…Smith et al [2] performed a regional flood frequency analysis (RFFA) at global scale using 703 discharge gauges from the Global Runoff Data Centre (GRDC) and a global annual average rainfall dataset from World-Clim [3]. Regressions were used to calculate the mean annual flood and they concluded that the best regressions used just catchment area and annual average rainfall as estimators.…”
Section: Introductionmentioning
confidence: 99%
“…In this test the statistic H is related to the variability of the at-site L-variation coefficient (L-CV) over a region (e.g. Alila, 1999;Burn and Goel, 2000;Castellarin et al, 2001;Shu and Burn, 2004;Smith et al, 2015;Ouarda, 2016).…”
Section: Introductionmentioning
confidence: 99%